The role of digital technologies for live display in the modern advertising industry (Journal of the College of Basic Education, 2025)
The radical transformations that have taken place in the world of advertising industry to transform it from the traditional digital format to the modern digital form have made it an important station for study. Live display programs supported by advanced digital technologies have become a driving force behind the success of advertising and increased interaction with it. Therefore, the research sheds light on how the use of this modern digital technology has affected the form of advertising and thus how it affects it, as it has become a driving force for the success of advertising campaigns. Therefore, the research focuses on the essential role that digital technologies play in creating advertisements that attract attention and build strong relationships between production companies and customers. In light of the extensive studies in the field of modern digital technologies, this research came to discuss one of the most important digital technologies in terms of development and modernity. The research problem crystallized with the following question:What is the role of digital technologies for live display in the modern advertising industry?The researcher then explained the importance of this study, which is highlighted by highlighting the capabilities, technologies and applications that shorten the time of producing the advertisement and raising the technical level and presenting it to the public, which makes it more influential and effective.Study ObjectiveTo identify the new cinematic techniques used in the production of advertisements to approach the reality of the film industry in form and art and bring about great development in the world of advertising industry.Research Limits The research is determined by the limits of the intentionally selected sample, which determines the time, place and subject of the study, which represents the research problem, which is an advertisement for the BMW car manufacturing company. Defining terms:The researcher defined an operational definition for the terms mentioned in the title, which require clarifying the researcher's intention by defining digital technologies. The researcher covered the methodological framework of the study and then proceeded with the second chapter, which is the theoretical framework and scientific basis for the research, which included two topics:The first topic: The concept of live display techniques.The second topic: Creative components in modern television advertising.The researcher concluded after the detailed study with a set of indicators that are considered a standard tool in analyzing the research sample.The researcher then reviewed the most important studies that approached the subject of her research and the most important points in common between the two studies, which are ((Simplicity and complexity in the structure of digital advertising design.) by the researcher (Wafaa Jassim Muhammad)).Then she addressed the third chapter, which includes the research procedures, including:Research methodology: The researcher relied on the descriptive analytical method in completing this research, which is defined as "describing what exists and includes describing the current phenomenon, its composition, operations, and prevailing conditions, recording, analyzing, and interpreting it."Research tool: These are the indicators that the researcher concluded from studying the theoretical framework.Research sample: An advertisement for the BMW car manufacturing company, produced in 2019. As for the unit of analysis: The researcher relied on the shot or scene, which represent the techniques used to show the visual structure in the shot - the scene as a main unit of analysis, as they represent the basic structural units within the visual achievement.Analysis: The researcher applied the standard tools to the sample and reached a set of results that she reviewed in the fourth chapter, including the most prominent:1- The live display technique contributes to expanding the creative range in presenting the new organization of complex visual elements to attract the viewer's attention in the first moments of the advertisement.2-Using the direct display mechanism constitutes an effective reduction of production costs and reduces production errors to the maximum possible extent. The study then concluded with a list of sources that the researcher used in the research text and an abstract in Englis